A Study of Fairness in the Practice of Weighing Palm Oil Buying and Selling at PT Pelindo Era Wira Forestama - Aldo, Muhammad; Musthofa, M. Arif; Sunarti, Zeni (CV. Zabags Qu Publish, 2025)
This study analyzes fairness and transparency in palm oil weighing at PT Pelindo Era Wira Forestama, integrating operational and ethical perspectives. A qualitative-descriptive approach was employed, involving observation, semi-structured interviews with staff and smallholder farmers, and document analysis. Results indicate persistent challenges, including discrepancies in weight measurements, restricted farmer access to scale data, and an inadequate complaint mechanism, which affect economic outcomes and ethical accountability. From an Islamic economics standpoint, these practices do not fully uphold the principles of justice (‘adl) and honesty (shidq), essential for equitable transactions. Recommendations include providing real-time scale access for farmers, establishing a transparent grievance system, and conducting periodic independent audits to ensure reliability and fairness. Implementing these strategies can enhance operational integrity, build trust with farmers, and align corporate practices with ethical and religious standards. The study contributes to understanding how operational reforms can promote just, responsible, and sustainable palm oil trade.